Economic Effect of Soil Health Card Scheme on Farmer’s Income: A Case Study of Gwalior, Madhya Pradesh (Indian Journal of Extension Education, 2019)
The study was undertaken to assess the economic effect of Soil Health Card Scheme on Income of Farmer’s by studying the economics of cultivation of three major rabi crops Wheat, Mustard and Chickpea in district Gwalior of Madhya Pradesh State during 2018-19. The samples composed of total 120 farmers of four blocks of district Gwalior. The yield of wheat, mustard and chickpea increased by 23.13 per cent, 20.01 per cent and 36.55 per cent, respectively after adoption of soil test based RDF. Further, higher net returns increased 25.22 per cent in wheat, 8.18 per cent in mustard 20.81 per cent in chickpea after soil test based fertilizer application. The B:C ratio increased from 3.92 to 4.13 in wheat, 3.09 to 3.20 in mustard and 3.34 to 3.57 in chickpea on adoption of soil test based RDF by the farmers. Thus, soil health card scheme was found highly beneficial to the farmers in term of increasing their income. However, there is a need to generate awareness about the benefits of this scheme among the farmers on one hand and strengthening of soil testing services / laboratories on the other hand for a wider adoption of soil test based RDF.